Influence of Lysogeny of Tectiviruses GIL01 and GIL16 on Bacillus thuringiensis Growth, Biofilm Formation, and Swarming Motility - Gillis, Annika (Appl Environ Microbiol, 2014)
Bacillus thuringiensis is an entomopathogenic bacterium that has been used as an efficient biopesticide worldwide. Despite the fact that this bacterium is usually described as an insect pathogen, its life cycle in the environment is still largely unknown. B. thuringiensis belongs to the Bacillus cereus group of bacteria, which has been associated with many mobile genetic elements, such as species-specific temperate or virulent bacteriophages (phages). Temperate (lysogenic) phages are able to establish a long-term relationship with their host, providing, in some cases, novel ecological traits to the bacterial lysogens. Therefore, this work focuses on evaluating the potential influence of temperate tectiviruses GIL01 and GIL16 on the development of different life traits of B. thuringiensis. For this purpose, a B. thuringiensis serovar israelensis plasmid-cured (nonlysogenic) strain was used to establish bacterial lysogens for phages GIL01 and GIL16, and, subsequently, the following life traits were compared among the strains: kinetics of growth, metabolic profiles, antibiotics susceptibility, biofilm formation, swarming motility, and sporulation. The results revealed that GIL01 and GIL16 lysogeny has a significant influence on the bacterial growth, sporulation rate, biofilm formation, and swarming motility of B. thuringiensis. No changes in metabolic profiles or antibiotic susceptibilities were detected. These findings provide evidence that tectiviruses have a putative role in the B. thuringiensis life cycle as adapters of life traits with ecological advantages.